Consolidaç\~ao do gasto com aç\~oes e serviços públicos de saúde: Trajetória e percalços no período de 2003 a 2017 - Sérgio F. Piola; Rodrigo Pucci de Sá e Benevides; Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This text presents a consolidation of Brazilian public health spending (ASPS) of the three spheres of government in the period 2003 to 2017. The main objective, besides analyzing the evolution of expenditure since the approval of the Constitutional Amendment 29 in 2000 (CA 29), is to demonstrate the expenditure distribution by geographic regions. We used public health spending data from Information System on Public Budgets in Health, and data available by the Ministry of Health (MoH) about federal health spending by states for the regionalization of the federal resources to ASPS. We have found that there was increasing of the binding resources to health by the three spheres. However, this increase was insufficient to reduce regional inequalities more significantly, since the necessary changes in the allocation criteria of the resources transferred by the MoH were not implemented, in order to meet the objectives defined by EC 29 and the law 141/2012 with regard to the allocation of the resources by the Union. Finally, we observed a fall in the applications in the years 2015 and 2016, a situation that was only temporarily temporized in 2017, because the final percentage of 15% of Net Current Revenue as the federal minimum spending on health was anticipated with the approval of the Constitutional Amendment 95 in 2016.
Keywords: H51; I180; 330; health financing; health expenditure; public finance; public health